Altitude‐Related Variation in Carbon, Nitrogen, and Phosphorus Contents and Their Stoichiometry of Woody Organs in the Subtropical Mountain Forests, South China - Chunlin Huo; Zhonghua Zhang; Gang Hu; Yinghua Luo (Ecology and Evolution)
ABSTRACT Altitude‐induced variations in hydrothermal conditions and vegetation affect plant nutrients and induce tradeoffs in survival strategies. However, nutrient allocation to different plant organs along altitudinal gradients remains unclear. Here, 24 plots were established across eight altitudinal gradients (300, 500, 700, 900, 1100, 1200, 1300, and 1400 m) in subtropical forests on Daming Mountain, South China. We analyzed the altitudinal patterns and factors influencing carbon (C), nitrogen (N), and phosphorus (P) content and their ratios in the leaves, branches, and roots of woody plants. We found that branches had higher mean C content and C:N and C:P ratios than roots and leaves, leaves had higher N and P content than roots and branches, and roots exhibited a higher mean N:P ratio than the other organs. With increasing altitude, the leaf and branch C, C:N, and leaf C:P increased, whereas the leaf N and P, branch N and N:P, and root N:P decreased. Plant N:P ratios above 16 indicate that plant growth in the study area was mainly restricted by P. The positive correlation between N and P content across plant organs suggests synergistic absorption of these nutrients by plants. These results demonstrate that soil nutrients and stoichiometry directly influenced C, N, and P stoichiometry among different organs and that the soil C:P ratio was a common impact factor for these organs. These findings may elucidate the nutrient allocation patterns and adaptive strategies of plants in subtropical mountains and provide a foundation for forest management and restoration.